2013
DOI: 10.1073/pnas.1220176110
|View full text |Cite
|
Sign up to set email alerts
|

SOX2–LIN28/let-7 pathway regulates proliferation and neurogenesis in neural precursors

Abstract: The transcription factor SRY (sex-determining region)-box 2 (SOX2) is an important functional marker of neural precursor cells (NPCs) and plays a critical role in self-renewal and neuronal differentiation; however, the molecular mechanisms underlying its functions are poorly understood. Using human embryonic stem cellderived NPCs to model neurogenesis, we found that SOX2 is required to maintain optimal levels of LIN28, a well-characterized suppressor of let-7 microRNA biogenesis. Exogenous LIN28 expression res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
185
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 55 publications
6
185
0
Order By: Relevance
“…In our previous study focusing on the LIN28 gene, which is fully active in NPCs, we found that SOX2 promotes an open chromatin state at the promoter (H3K9ac mark) through recruitment of the TRRAP/GCN5 complex (56). Here, we uncovered a distinct epigenetic mechanism of SOX2 function on poised proneural and early neurogenic genes in NPCs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In our previous study focusing on the LIN28 gene, which is fully active in NPCs, we found that SOX2 promotes an open chromatin state at the promoter (H3K9ac mark) through recruitment of the TRRAP/GCN5 complex (56). Here, we uncovered a distinct epigenetic mechanism of SOX2 function on poised proneural and early neurogenic genes in NPCs.…”
Section: Discussionmentioning
confidence: 61%
“…The cell-cycle deficits observed in these proliferating cells likely result from the reduced expression of Lin28. Our previous work showed that SOX2 directly controls Lin28 expression in several types of NPCs, and Lin28 rescues the proliferation defect in SOX2-deficient NPCs through effects on cell-cycle regulators such as CyclinD1, TLX, and CDC25A (56). On the other hand, the absence of a cell-cycle deficit in SOX2-deficient radial glia stem cells is consistent with the limited self-renewal of this stem cell population (48).…”
Section: Discussionmentioning
confidence: 69%
“…Recently, Wang et al [5] reported that SOX2 knockdown (KD) caused a compensational increase in SOX3 expression and that simultaneous depletion of SOX2 and SOX3 led to primitive streak induction in hESCs. Also, SOX2 KD was reported to affect hNPCs proliferation and neurogenesis rather than apoptosis through a SOX2-Lin28/let7 pathway [6]. Apart from these studies, how SOX2 exerts cell type-dependent roles in these two distinct and developmentally related cell types is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2). Because Sox2 has recently been shown to bind to the promoters of poised pro-neural genes in NPCs to enable an appropriate neuronal differentiation (32,35) program, including the neurogenic genes Ngn2 and NeuroD1, we reasoned that RIT1-dependent neurogenic gene expression might rely on Sox2 activation. Indeed, active RIT1 expression both increases Sox2 protein levels (Fig.…”
Section: Discussionmentioning
confidence: 99%